ECONOMIC DAMAGE OF PNEUMOCOCCAL VACCINATION ABSENCE AS A RISK FACTOR FOR COMPLICATIONS OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE - E. A. Orlova; I. P. Dorfman; A. R. Umerova; B. I. Kantemirova; M. A. Orlov; M. A. Abdullaev (Фармация и фармакология (Пятигорск), 2022)
The aim of the article is the evaluation of the economic damage (ED) because of the absence of pneumococcal vaccination as a leading risk factor for the development of community-acquired pneumonia (CAP) and acute exacerbations of а chronic obstructive pulmonary disease (COPD).Materials and methods. The method of attributive statistics was used for the first time to assess the ED of the vaccination absence as an independent risk factor contributing to the development of CAP and COPD exacerbations in the Astrakhan region for the period of 2015–2019. To do this, at the beginning of the study based on the literature data, a relative risk of COPD complications associated with the absence of pneumococcal vaccination was determined. Using it as a risk factor, prevalence rates (a proportion of non-vaccinated patients with COPD), the population attributable risk (PAR) was calculated. Further, the annual economic damage (ED) from the development of CAP and COPD exacerbations was determined. To assess the cost-effectiveness of the COPD complications prevention, vaccination costs of newly registered patients were calculated and the ratio of these costs to the average annual ED was determined.Results. A decrease in the non-vaccinated patients’ proportion corresponds to the decrease in the total ED from COPD complications: from 13.16 million rubles to 6.06 million rubles during the observation period. The calculations showed that due to the increase in the vaccinated patients’ proportion over a five-year observation period, the ED from the CAP development decreased by 2.1 times, from exacerbations of COPD – by 2.3 times. The vaccination costs of newly diagnosed COPD cases amounted to 0.63 million rubles. Thus, to prevent the annual ED of 3.24 million rubles, the sum for the state to spend, should be 5.2 times as small.Conclusion. A study on the evaluation of the ED due to the risk factor (RF), the pneumococcal vaccination absence, showed that its elimination reduces the risk of acute COPD exacerbations and the development of CAP, as well the ED, as associated with them. Reducing the economic costs of the health care system with significantly lower vaccination costs, makes this preventive measure economically viable.